Autumn and winter kidney fat indexes of roe deer does and their correlation with reproductive parameters - Majzinger, István (Acta Agraria Debreceniensis, 2013)
I studied the variations of kidney fat indexes (KFI) in two game management units of the Great Hungarian Plain between 2002 and 2004 in the autumn and winter months. I was looking for correlation between the autumn and winter KFI as well as between the autumn KFI and reproductive parameters (number of corpora lutea, recruitment rate). There was a significant positive correlation between the average winter and the average next autumn KFI (r=0.991, p<0.1). The average winter KFI showed strong positive correlation with the average number of corpora lutea (CL) in the next rutting season (r=0.978, p<0.05). The average autumn KFI and the average grown up offspring showed positive but not significant correlation (r=0.725, p=0.275).